2021
DOI: 10.1038/s41560-021-00888-5
|View full text |Cite
|
Sign up to set email alerts
|

Role of the social factors in success of solar photovoltaic reuse and recycle programmes

Abstract: By 2050, the cumulative mass of end-of-life photovoltaic (PV) modules may reach 80 Mt globally. The impacts could be mitigated by module recycling, repair and reuse; however, previous studies of PV circularity omit the consideration of critical social factors. Here we used an agent-based model to integrate social aspects with techno-economic factors, which provides a more realistic assessment of the circularity potential for previously studied interventions that assesses additional interventions that cannot be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(37 citation statements)
references
References 59 publications
0
37
0
Order By: Relevance
“…In the same year, Walzberg et al (2021) have also demonstrated the implementation of an ML metamodel to investigate the influence of social aspects (peer attitude and influence) in solar photovoltaic (PV) reuse and recycle programs. The developed ML metamodel is considered wellsuited for this study due to its ability to consider temporal aspects, adopts a systemic approach, account for human decisions and interactions between actors, and utilize current developments in behavioral economics and psychology.…”
Section: Machine Learning (Ml)mentioning
confidence: 99%
“…In the same year, Walzberg et al (2021) have also demonstrated the implementation of an ML metamodel to investigate the influence of social aspects (peer attitude and influence) in solar photovoltaic (PV) reuse and recycle programs. The developed ML metamodel is considered wellsuited for this study due to its ability to consider temporal aspects, adopts a systemic approach, account for human decisions and interactions between actors, and utilize current developments in behavioral economics and psychology.…”
Section: Machine Learning (Ml)mentioning
confidence: 99%
“…PV ICE can take the outputs of various decision models and quantify the effects of different waste-management intervention scenarios, such as those from Walzberg et al. ( Walzberg et al., 2020 ; Walzberg et al., 2021 ), as explored in Hegedus et al. ( Hegedus et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it is expected that the amount of silver used, which was approximately 10 µg per cell in 2021, will be reduced by almost half by 2032 [37]. Therefore, the most desirable method of recycling a PV module is to recover the performance of the module at the end of its commercial life and use it again [38][39][40]. In particular, a technology to normalize the system by recovering defects in PV modules with severe power degradation in PV power plants, currently operating under the renewable portfolio standard (RPS) subsidy system, is essential.…”
Section: Introductionmentioning
confidence: 99%